PENERAPAN TARI BATOK DI TAMAN KANAK-KANAK ADHYAKSA PADANG - Sahrani Asiva; Indra Yeni; Farida Mayar; Yul Syofriend (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of batok dance at Adhyaksa Padang Kindergarten, including activity planning, training stages, and factors supporting its success. The study used a descriptive qualitative approach. The research informants consisted of school principal and teachers involved in batok dance activities. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results of the study showed that the implementation of batok dance had been planned systematically through the preparation of school programs, teaching modules, activity objectives, selection of movements that were appropriate to the characteristics of the children, and scheduling of exercises. The training stages are carried out in stages starting from the introduction of coconut shells, basic movements, practice with musical accompaniment, to evaluation. Factors supporting the success of the activity included children’s motivation teacher competence, parental support, the availability of facilities and infrastructure, the use of music, and a school environment that supports children’s artistic development. The coconut shell dance not only functions as an artistic activity but also contributes to the development of kinesthetic intelligence, creativity, and self confidence in early childhood.